2017
DOI: 10.1002/hrm.21845
|View full text |Cite
|
Sign up to set email alerts
|

Disability status, individual variable pay, and pay satisfaction: Does relational and institutional trust make a difference?

Abstract: Although prior research suggests that disabled employees have different needs in the context of some HRM practices, we know little about their reactions to reward systems. We address this gap in the literature by testing a model using the 2011 British Workplace Employee Relations Survey (disabled employees, n = 1,251; nondisabled employees, n = 9,959; workplaces, n = 1,806) and find that disabled employees report lower levels of pay satisfaction than nondisabled employees, and when compensated based on individ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 107 publications
1
25
0
Order By: Relevance
“…These findings can help HR departments to develop strategies to attract, engage, and retain these employees, who are a priority for organizations today, given that disabled individuals constitute an underused labor pool and can offer organizations the benefits of diversity (Shantz et al, 2018).…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…These findings can help HR departments to develop strategies to attract, engage, and retain these employees, who are a priority for organizations today, given that disabled individuals constitute an underused labor pool and can offer organizations the benefits of diversity (Shantz et al, 2018).…”
Section: Discussionmentioning
confidence: 95%
“…Despite the many studies addressing JS, not much research has explored the JS of people with disabilities (Houser and Chace, 1993;Rodríguez et al, 2014;Baumgärtner et al, 2015;Pagán-Rodríguez, 2015;Park et al, 2016;Akkerman et al, 2017Akkerman et al, , 2018Kocman and Weber, 2018;Shantz et al, 2018). Akkerman et al (2016) affirm that little is known about the JS of employees with disabilities, but given the enormous significance of work in people's lives, awareness of their JS is essential.…”
Section: Theoretical Framework and Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation
“…To which they can respond: No; Yes, limited a little; Yes, limited a lot. As in Hoque et al (2017) and Shantz et al (2018), employees are defined as disabled (9.7 per cent) if they are either limited a little or a lot. This approach is consistent with the definition in the LFS which is used to track progress on UK government disability commitments.…”
Section: Disabilitymentioning
confidence: 99%
“…In pay satisfaction literature, a considerable number of studies identified gender differences, showing that men are less satisfied with their pay (e.g. Balkin and Gomez-Mejia, 2002;Ataay, 2018;Shantz et al, 2018). The meta-analysis conducted by Williams et al (2006) showed that, when controlling for actual pay, "women were slightly more satisfied with their pay than are men".…”
Section: Work Orientationmentioning
confidence: 99%